This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: STAT 410 Fall 2011 Homework #6 (due Friday, October 14, by 3:00 p.m.) 1  4. Let X 1 , X 2 , , X n be a random sample from the distribution with probability density function ( )( )( ) g 1 1 g g ; X x x f + = , 0 < x < 1, > 1. 1. a) Obtain the method of moments estimator of , g ~ . E ( X ) = ( )( ) g + 1 g 1 1 g dx x x y = 1 x dy = dx = ( ) ( ) g + 1 g 1 1 g dy y y = ( ) ( ) g g + + + 1 1 1 g g 1 1 g g dy y dy y = 2 g 1 g 1 + + = 2 g 1 + . OR E ( X ) = ( )( ) g + 1 g 1 1 g dx x x u = x dv = ( )( ) g 1 1 g x + dx du = dx v = ( ) 1 g 1 + x = ( ) ( ) g + + + 1 1 1 1 g g 1 1 dx x x x = ( ) g + 1 1 g 1 dx x = 2 g 1 + . OR Beta distribution, = 1, = + 1. G E ( X ) = G + = 2 g 1 + . 2 g ~ 1 X X 1 1 + = = = n i i n G 2 X 1 X X 2 1 g ~ = = . b) Obtain the maximum likelihood estimator of , g . Likelihood function: L ( ) = ( ) ( ) ( ) ( ) g g 1 1 X 1 1 X 1 1 g g  + + = = = n i i n n i i . ln L ( ) = ( ) ( ) = + + n i i n 1 X 1 g 1 ln g ln . () ( ) ( ) = + + = n i d d i n 1 X 1 1 g g L g ln ln = 0. G ( ) = = n i i n 1 X 1 1 ln g . 2. a) What is the probability distribution of W = ln ( 1 X ) ? Let W = ln ( 1 X ) . F X ( x ) = ( )( ) g + x dy y g 1 1 g = ( ) 1 1 g x y + = ( ) 1 g 1 1 + x , 0 < x < 1. F W ( w ) = P ( W w ) = P ( ln ( 1 X ) w ) = P ( X 1 e w ) = 1 e ( +1 ) w , 0 < w < . OR X = 1 e W = g 1 ( W ) d x / d w = e w f W ( w ) = f X ( g 1 ( y ) ) w x d d = ( ) ( ) 1 g g w w e e + = ( + 1 ) e ( +1 ) w , 0 < w < . G The distribution of W is Exponential with mean 1 g 1 + . b) What is the probability distribution of Y = ( ) g = n i i 1 X 1 ln = g = n i i 1 W ? The distribution of W is Exponential with mean 1 g 1 + . G Y = g = n i i 1 W has Gamma ( = 2 n , usual = 1 g 1 + ) distribution. c) Is the maximum likelihood estimator of , g , an unbiased estimator of ? If g is not an unbiased estimator of , construct an unbiased estimator g of based on g . E ( Y 1 ) = ( ) () ( ) + + 1 1 g 1 1 g dx x n x x n n e = ( ) ( ) ( ) ( ) ( )  + + + 1 2 1 g 1 1 1 1 g g dx x n n x n n e = 1 1 g + n . Therefore, E ( g ) = ( ) 1 1 1 g + +...
View
Full
Document
 Fall '08
 Monrad
 Statistics

Click to edit the document details